Stock market volatility in Malaysia sectoral indices during the general election - Chia, Ricky Chee Jiun (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the effect of general election on the Malaysian stock market for the period of January 1994 to December 2015. The empirical model used in this study follows the Threshold GARCH model developed by Glosten et al. (1993), to investigate the stock returns and return volatility of the FTSE Bursa Malaysia KLCI and ten selected main sectoral indices before and after the elections. The selection of the event window is in line with the Malaysian general election process. Moreover, the full sample is divided into two sub-samples (1994-2005 and 2006-2015) to avoid erroneous inferences, and to reflect the real stock market volatility under two different political situation. Generally, results from statistical analysis uncover significant pre-general election effect and post-general election effect from the five most recent general elections held in Malaysia. Interestingly, the two sub-samples showed different election effect on stock market volatility. Most of the sectoral indices have lower volatility before general election and higher volatility after general election in the sub-sample period of 1994-2005. Remarkably, during the 2008 and 2013 general election years, political uncertainty due to the close fight between the two major political parties showed up its negative and significant influence in the stock market volatility before general election. The major implication of these findings is that while investors seek abnormal returns on certain sectors during the next general election, they will have to pay attention to the influence of political uncertainty on the stock market return during the general election year.